2014
DOI: 10.1007/s40279-014-0162-1
|View full text |Cite
|
Sign up to set email alerts
|

Interference between Concurrent Resistance and Endurance Exercise: Molecular Bases and the Role of Individual Training Variables

Abstract: Concurrent training is defined as simultaneously incorporating both resistance and endurance exercise within a periodized training regime. Despite the potential additive benefits of combining these divergent exercise modes with regards to disease prevention and athletic performance, current evidence suggests that this approach may attenuate gains in muscle mass, strength, and power compared with undertaking resistance training alone. This has been variously described as the interference effect or concurrent tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
221
0
14

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 257 publications
(250 citation statements)
references
References 176 publications
6
221
0
14
Order By: Relevance
“…Further work is required to define the molecular events that mediate chronic phenotypic adaptations to training and potentially their progression during a training program. Such information is likely to also provide further mechanistic insight into the concurrent interference effect (38). We also conducted all muscle analyses using mixed whole muscle homogenate, which may have masked any fiber-type specific differences in measured postexercise responses, including glycogen content, signaling responses and gene expression (65).…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further work is required to define the molecular events that mediate chronic phenotypic adaptations to training and potentially their progression during a training program. Such information is likely to also provide further mechanistic insight into the concurrent interference effect (38). We also conducted all muscle analyses using mixed whole muscle homogenate, which may have masked any fiber-type specific differences in measured postexercise responses, including glycogen content, signaling responses and gene expression (65).…”
Section: Limitationsmentioning
confidence: 99%
“…From a practical standpoint, elucidation of the roles of specific training variables (e.g., training intensity, volume, and modality) is required to inform exercise prescription guidelines for minimizing potential interference during concurrent training (38). One important practical consideration is the intensity of endurance training employed in a concurrent training program.…”
mentioning
confidence: 99%
“…Concurrent exercise involves the simultaneous incorporation of both endurance and resistance exercise, (Fyfe et al, 2014) and is a prevalent training method for elite and recreational athletes that are aiming to elicit divergent physiological adaptations in parallel. Previous work examining recovery from EIMD has used resistance (Harrison andGaffney, 2004, Miyama andNosaka, 2004) or endurance (Bell et al, 2014, Betts et al, 2009) stimuli in isolation.…”
mentioning
confidence: 99%
“…Specifically, the muscle-specific overexpression of 4EBP1 in mice has been shown to promote increases in mitochondrial markers (Tsai et al, 2015). Therefore, it remains possible that gastrocnemius MPS was lower in EX rats because of the endurance-type phenotype that this model imposes, as certain literature suggests that endurance training can reduce MPS levels and anabolic skeletal muscle signalling (Fyfe, Bishop, & Stepto, 2014;Hawley, 2009). It should be noted, however, that Mosoni and coworkers (Mosoni et al, 1995) reported that 30 weeks (5 days/week) of treadmill training in rats does not alter basal tibialis anterior MPS rates and increases basal soleus MPS rates by 71%.…”
Section: Discussionmentioning
confidence: 99%